THE IMPACT OF FEMALE DIRECTORS, PROFITABILITY, AND CEO AGE ON CARBON EMISSION DISCLOSURE: THE MODERATING ROLE OF INSTITUTIONAL OWNERSHIP IN INDONESIA - Erna Wati; Sheila Septiany; Febrianti Saniapon (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2026)
This study investigates the effect of female directors, defined as women serving on the board of directors within Indonesia's two-tier governance system, profitability, and CEO age on carbon emission disclosure, with institutional ownership assessed as a moderating variable. The research is driven by the persistently limited transparency of carbon emissions in Indonesia and the need to understand how governance attributes contribute to environmental accountability. A quantitative approach is applied using secondary data from non-financial firms listed on the Indonesia Stock Exchange for the 2020–2024 period. The analysis employs fixed-effect panel regression with robust standard errors, incorporating logarithmic transformations to ensure model stability and interpretability. The empirical results show that female directors on the board of directors have a significant negative effect on carbon emission disclosure, while profitability and CEO age exhibit no direct influence. The moderation analysis indicates that institutional ownership weakens the effect of profitability, strengthens the influence of CEO age, and shows no moderating role in the relationship between female directors on the board of directors and disclosure. These findings imply that institutional investors in Indonesia remain financially driven, although they tend to reinforce the long-term orientation of senior CEOs in promoting transparency. Overall, this study underscores the importance of aligning governance mechanisms with stakeholder expectations to advance carbon emission disclosure as a substantive component of corporate sustainability. .